ANALYSIS OF CONSUMER SATISFACTION AND LOYALTY BASED ON THE GREEN MARKETING CONCEPT OF PT UNILEVER INDONESIA TBK - Yepri Endika; Eny Sulistyowati; Faizul Farkhan (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to comprehensively analyze how PT Unilever Indonesia Tbk implements green marketing concepts and how these are articulated in their annual reports from 2020 to 2024, as well as their connection to consumer satisfaction and loyalty. Employing a qualitative approach with a case study design, this research focuses on document analysis, particularly the company's annual reports, as the primary data source. Green marketing analysis indicators include corporate commitment, green products, green place/distribution, and green promotion. Concurrently, consumer satisfaction indicators refer to company statements regarding positive consumer responses and a focus on sustainability preferences, while consumer loyalty is measured by claims of brand strengthening, consumer involvement in sustainability programs, and brand differentiation. The analysis reveals that PT Unilever Indonesia Tbk consistently integrates sustainability principles into their core business, reflecting green marketing as a holistic strategy aimed at building trust, meeting ethical expectations, and ultimately driving consumer satisfaction and loyalty. Narratives within the annual reports explicitly link green initiatives to positive consumer responses and enhanced brand loyalty, indicating that the company views green marketing as a crucial element in fostering long-term relationships with its customers. This study is expected to provide valuable insights into corporate sustainability communication strategies and their implications for consumer behavior within the Indonesian market context.